2012
DOI: 10.1021/np300109s
|View full text |Cite
|
Sign up to set email alerts
|

Naphthomycins L–N, Ansamycin Antibiotics from Streptomyces sp. CS

Abstract: Previous analyses of the naphthomycin biosynthetic gene cluster and a comparison with known naphthomycin-type products from Streptomyces sp. CS have suggested that new products can be found from this strain. In this study, screening by LC-MS of Streptomyces sp. CS products formed under different culture conditions revealed several unknown peaks in the product spectra of extracts derived from oatmeal medium cultures. Three new naphthomycins, naphthomycins L (1), M (2), and N (3), and the known naphthomycins A (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Thiol-containing compounds such as ethanethiol, glutathione (GSH), N-acetyl-L-cysteine, and so on, can also react chemically with benzoquinone or naphthoquinone ansamycins, producing many semisynthetic or natural thioansamycins. 12,20,21 Recently, Yang et al 22 reported two thionaphthomycins (naphthomycins M and N). Naphthomycin M contains a thioglycolic acid group connected to C-30 of the naphthomycin skeleton via sulfur, and naphthomycin N is a dimer-like molecule, with a 2-aminoethanethiol group as bridge to connect two naphthomycin monomers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thiol-containing compounds such as ethanethiol, glutathione (GSH), N-acetyl-L-cysteine, and so on, can also react chemically with benzoquinone or naphthoquinone ansamycins, producing many semisynthetic or natural thioansamycins. 12,20,21 Recently, Yang et al 22 reported two thionaphthomycins (naphthomycins M and N). Naphthomycin M contains a thioglycolic acid group connected to C-30 of the naphthomycin skeleton via sulfur, and naphthomycin N is a dimer-like molecule, with a 2-aminoethanethiol group as bridge to connect two naphthomycin monomers.…”
mentioning
confidence: 99%
“…But the (bio)synthetic mechanism(s) of naphthomycins M and N remains unclear. 22 Ō mura 23 and Shibata 24 reported chemical modification of herbimycin A, and obtained more than a dozen herbimycin A derivatives with various modifications at C-17 or C-19 of the benzoquinone moiety of herbimycin A. Among them, derivatives with a methylpiperazino group or bromine substituent at C-19 showed high antitumor activity.…”
mentioning
confidence: 99%
“…Hence, in order to make the training stable and comparison fair, we created two different datasets: SMART5 and SMART10, containing all spectra of compound families ( e.g . veraguamides 64 , ebractenoids 57 , naphthomycins 65 , viequeamides, etc.) with at least 5 and 10 HSQC spectra, respectively, per family.…”
Section: Methodsmentioning
confidence: 99%
“…With reference to to reports , compounds 5 and 14 were tentatively identified as magnoflorine and amurine. Compound 29 exhibited [M+H] + ion at m/z 284, [M+H–137] + ion at m/z 147 and [M+H–137–CO] + ion at m/z 119, and therefore was assigned as N ‐ p ‐hydroxyl‐ trans ‐coumaroyltyramine .…”
Section: Resultsmentioning
confidence: 99%